DIAGNOSIS AND MANAGEMENT OF ATRESIA ANI IN NEWBORN INFANTS: LITERATURE REVIEW - Hapsari, Ariadne Tiara (Mandala Of Health, 2023)
Anal atresia or anorectal malformation (MAR) or imperforate anus is a congenital abnormality that includes the distal anus, rectum and also the urogenital tract. Is a congenital abnormality that is often encountered in pediatric surgery cases. This condition has varying degrees of severity ranging from imperforate anal membrane to complete caudal regression. History and physical examination are very important in diagnosing anorectal malformations. Treatment of atresia ani consists of surgery to create an artificial anal opening and rectal muscle reconstruction. Surgery is performed within the first 48 hours of birth to prevent infection and other complications. The prognosis for atresia ani is generally good if treated properly. Postoperative care and long-term follow-up are important to monitor rectal function and defecation.